Selected adjustment factors, study habits and academic achievement of dormitory and non-dormitory residents of Philippine Science High School. - Tuazon, Ludivina Henson (s. n., 1975)
One hundred forty dormitory residents and 125 non-dormitory residents of the freshmen and sophomore classes of the Philippine Science High School enrolled during the SY 1973-1974 were administered the Brown-Holtzman Survey Habits and Attitudes (SSHA) and the Bell Adjustment Inventory Revised (1962) Student Form. Non-dormitory residents possess relatively better study habits and attitudes than the dormitory residents although these tend to be generally similar for both groups. Among the freshmen, the non-dormitory residents both male and female registered better study habits and attitudes and more homogeneity in SSHA scores than the dormitory residents. Among the sophomores, the male dormitory and the female non-dormitory residents indicate better study habits and more homogeneity in their responses on the SSHA than the male non-dormitory and the female dormitory residents. Study habits are correlated to academic achievement, submissiveness, and emotionality. Home adjustment is correlated to emotionality, and health adjustment to submissiveness.